Treatment patterns of childhood diarrhoea in rural Uganda: a cross-sectional survey - Löfgren Jenny; Tao Wenjing; Larsson Elin; Kyakulaga Francis; Forsberg Birger C (BMC, 2012)
Abstract Background Diarrhoea is the second leading cause of death in children under five accounting for 1.8 million deaths yearly. Despite global efforts to reduce diarrhoea mortality through promotion of proper case management, there is still room for ample improvement. In order to seek options for such improvements this study explored the knowledge and practices of diarrhoea case management among health care providers at health centres and drug shops in Uganda. Methods Records were reviewed for case management and structured interviews concerning knowledge and practices were conducted with the staff at all health centres and at all identified drug shops in the rural district of Namutumba, Uganda. Results There was a significant gap between knowledge and documented practices among staff. Antibiotics, antimalarials and antipyretics were prescribed or recommended as frequently as Oral Rehydration Solution (ORS). In almost a third of the health facilities, ORS was out of stock. 81% of staff in health centres and 87% of staff in drug shops stated that they prescribed antibiotics for common diarrhoea. Zinc was not prescribed or recommended in any case. Conclusions The findings indicate that many children presenting with diarrhoea are inadequately treated. As a result they may not get the rehydration they need and are at risk of potential side effects from unjustified usage of antibiotics. Practices must be improved at health centres and drug shops in order to reduce childhood mortality due to diarrhoeal diseases.